Role of B Type Natriuretic Peptide in the Early Diagnosis of Left Ventricular Diastolic Dysfunction in High Risk Subjects - Hoque, S; Rahman, MA; Haque, MJ; Khan, AR; Rahman, MS; Hoque, MM; Hossain, N (Cardiovascular Journal, 2010)
Background: Brain natriuretic peptide (BNP) reflects left ventricular pressure. It increases in systolic dysfunction. Our aim was to evaluate role of plasma BNP level in early diagnosis of left ventricular isolated diastolic dysfunction. Methods: We studied 60 patients (male=18, female=42) with hypertension, diabetes mellitus, ischemic heart disease, dyslipidemia. The Doppler parameters used for evaluation of diastolic dysfunction are: isovolumetric relaxation time (IVRT), Transmitral flow velocities (E/A) ratio, deceleration time (DT) & pulmonary vein Doppler findings. 49 patients (group-1) had diastolic dysfunction whereas 11 patients (group-2) had normal flow patterns. Plasma BNP level was done in all patients. Results: Mean plasma BNP levels were 40.41±6.82 pg/ml in individuals with normal filling patterns and 183.36±25.28 pg/ml in subjects with abnormal diastolic dysfunction (p<0.001).The accuracy of BNP in detecting diastolic dysfunction was assessed with receiver-operating characteristic(ROC) analysis. The area under the ROC curve for BNP test accuracy in detection of any abnormal diastolic dysfunction was 0.928 (95% CI, 0.861 to 0.994;p<0.001).A BNP value of 63 pg/ml had the sensitivity of 89.9%,specificity of 91.9% and accuracy of 90.3%.PPVwas 97.8% and NPV-66.7% for detecting diastolic dysfunction. Conclusion: Raised plasma BNP level is useful for early diagnosis of isolated left ventricular Diastolic dysfunction. Key words: BNP; Diastolic dysfunction. DOI: 10.3329/cardio.v3i1.6419 Cardiovasc. j. 2010; 3(1): 2-6